Glycogen Synthase Kinase-β3 in Ischemic Neuronal Death - Hanumanthappa, Pradeep; Densi, Asha; Golgodu Krishnamurthy, Rajanikant (Current Neurovascular Research, 2014)
Glycogen synthase kinase 3β (GSK-3β) is implicated in diverse cellular processes such as cell signaling and survival. Accumulating lines of evidence indicate that increased GSK-3β activity contributes to neuronal death and pathogenesis of ischemic stroke. Considering predominant roles of GSK-3β in neuronal apoptosis, modulation of this protein kinase is a reliable strategy for ischemic neuroprotection. In this review, we survey and synthesize the current knowledge about the role of GSK-3β in neuroprotection following the ischemic stroke.
Keywords: brain